Development of freezing process in presence of nanoparticles involving transient conduction heat transfer through finned wavy enclosure - Khalid H. Almitani; Nasrin B.M. Elbashir (Case Studies in Thermal Engineering, 2024)
The solidifying phenomena have been scrutinized in current work and techniques for expedition of process have been incorporated. The shape of geometry and shape of nanoparticles can alter the productivity of the unit. Utilizing higher concentration and bigger value of shape factor can accelerate the process. The present unsteady phenomena were simulated via Galerkin approach and to augment the accuracy, the shape of the mesh was adapted with location of the ice front. The existence of nanoparticles within water can enhance the freezing rate by about 26.73 %. The required time alters from 232.63s to 216.4s, when powders with bigger shape factor utilizes. Augment of concentration of powders from 0.02 to 0.04 can drop the solidification time around 13.78 %.